Organic composting of crab residue in coriander cultivation - Ramos, Mayra Oliveira; Ribeiro, Suezilde da Conceição Amaral (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The objective of this research was to evaluate the agronomic performance of coriander and the chemical characteristics of the soil under different organic fertilizations with crab residue. For the agronomic performance, the height, green and dry mass of the plants were collected. In the chemical analysis were determined the pH and the concentrations of 〖Ca〗^(2+), 〖〖Ca〗^(2+)+Mg〗^(2+), 〖Al〗^(3+),〖Na〗^+, Potential Acidity (H^++〖Al〗^(3+)), Organic Matter (O.M), Nitrogen (N) e Potassium (P). The treatments fertilized with the organic compounds that had gliricidia, dry leaves and 5% of crab residues had better agronomic performance. Regarding the chemical characteristics, the Hierarchical Grouping Analysis (AAH) allowed to identify the formation of three groups, which were united according to the amount of crab residues present in the treatments. And with the Principal Component Analysis (PCA) it was possible to identify that the addition of residues of the crab-uçá contributed to the increase the levels of 〖Ca〗^(2+), 〖〖Ca〗^(2+)+Mg〗^(2+),〖Na〗^+ and alkaline pH, and in the absence of 〖Al〗^(3+) and Potential Acidity (H^++〖Al〗^(3+)) in the soil.